Silicone loop alternative for posterior bitewing radiography - Shinta Amini Prativi; Shanty Chairani; Tyas Hestingsih (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Bitewing radiography is a technique that depicts the crown of the maxillary and mandibular teeth and the crest of the alveolar bone in the same receptor. The use of film holders and paper loops in bitewing techniques is very helpful in standardising radiographs, but it has some disadvantages, including the lack of efficiency and discomfort. Therefore, silicone has been widely used in the medical field as a replacement for paper loops. Purpose: This study was conducted to describe the compatibility of the silicone material as an alternative for bitewing radiography. Methods: This research is experimental and a one-shot case study. It used the Mann–Whitney (P < 0.05) test for statistical analysis to compare the results of the radiographs using silicone loops and paper loops and to analyse the quality of each radiograph: object coverage, density, contrast, sharpness, geometry, and overlapping. Results: The images where silicone loops were used show adequate results in six radiograph quality assessments. There was no significant difference between the radiographs that were obtained using the silicon loop and the paper loop (p > 0.05). Conclusion: Silicone loops can be an alternative tool for bitewing radiography because they result in optimal image quality.